ANALISIS HUKUM TERHADAP INFORMED CONSENT DALAM TINDAKAN MEDIS DI ERA DIGITAL: Legal Analysis of Informed Consent in Medical Actions in the Digital Era - Alfarizi, Lalu Mariawan; Listyaningrum, Novita (Ganec Swara, 2025)
Informed consent is a fundamental legal and ethical principle in medical practice that affirms the patient’s autonomy to make decisions based on complete and transparent information. The rapid digital transformation of health services in Mataram City—such as online registration systems, telemedicine consultations, and the implementation of digital signatures—has reshaped the legal framework of informed consent in Indonesia. This study aims to analyze the legal validity and implications of digital informed consent under Indonesian health law, as well as to identify mechanisms of patient protection in the digital era. Using a normative juridical method with statutory and conceptual approaches, this research examines relevant legislation, including the Medical Practice Law, the ITE Law, and the Personal Data Protection Law. The findings indicate that digital informed consent is legally valid as long as it fulfills the essential elements of a lawful agreement under Article 1320 of the Indonesian Civil Code and complies with Article 11 of the ITE Law regarding electronic signatures. However, regulatory gaps remain concerning technical procedures, authentication standards, and data protection mechanisms. Therefore, comprehensive regulations are urgently required to ensure legal certainty, medical accountability, and the protection of patient rights in Indonesia’s evolving digital health ecosystem.